STRATEGI ADAPTASI NELAYAN LANJUT USIA DAN HUBUNGANNYA DENGAN KETAHANAN SOSIAL. STUDI KASUS DI NAGARI AIR BANGIS, KECAMATAN SUNGAI BEREMAS, KABUPATEN PASAMAN BARAT - Ermayanti . (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2014)
Human existence as living beings will keep trying to make ends meet, despite his advanced age. Reality that they are not engaged by the employer group requiring them to implement various strategies in order to fulfill the necessities of life for yourself and family is maintained. This is possible as an option strategy adaptation in the elderly fishermen anticipate the changes that occur in the life of the fishing community. This study aims to describe the fishing community adaptation strategies in the face of the elderly. Future elderly fishing communities are determined based on the socio-cultural level of productivity that is generated, are still actively searching for fish on the high seas or just along the coast. Productive age limit directly affects the revenue lost fishermen. This fact led to the emergence of a variety of problems experienced by elderly fishermen, both from the economic, psychological, social and cultural. The families of elderly fisherman as the unit of analysis in this study have similar characteristics with elderly fishermen in general. A qualitative approach is emphasized in the process of collecting and analyzing the data. For that, although using the analysis in several families of elderly fishermen, but the problems are representative of elderly fisherman can span the 'hierarchy. The results showed that the main strategy applied elderly fisherman is still maintaining fishermen job, considering the social and cultural environment sulir fishing communities offer alternatives for another job. In addition, elderly family strategy in fulfilling its economy is the income earned, usually in debt to the tauke or indebted to anyone who would give him a loan debt. Aside from the elderly fisherman fishermen borrow another boat and look for alternative livelihoods outside between fishermen, such as gathering firewood to be sold to people in need. In addition, the results showed that elderly fisherman efforts to realize social security is to improve safety in these villages with mutual respect, tolerance and collaboration, because the villagers' Air Bangis already feel safe. In Nagari Air Bangis rarely finds conflicts between fishermen here, even if there was only a small problem, which can be directly solved maslaah. Usually the elderly fisherman to keep track of security among citizens just always maintain good relations between people, mutual help for anyone who needs and mutually saluted each other. Not distinguish economic status or the status of their fishermen. The main problem in this village is still the economic problems of society, because there are many people here who are in the poverty level.